Greening A Cuban Local Mango Supply Chain: Sustainability Options and Management Strategies - Giannetti, B.F.; Prevez, L.; Agostinho, F.; Almeida, C. M. V. B. (Journal of Environmental Accounting and Management, 2026)
Articulating all actors and activities of supply chain having an impact on sustainability is a complex task especially for a limited domestic market production sector. This complexity is the result of several factors, such as the quality of the product, the degree of competitiveness and the high costs of transactions, which arise from a small economic scale. This paper proposes a sustainability analysis using emergy accounting and the Cleaner Production approach applied to the case study of a mango pulp supply chain on a local level in Santiago de Cuba. The results obtained show that the current agricultural economy model is characterized by i) the use of chemical fertilizers, II) a large presence of labor and iii) a small use of natural resources. The cleaner production strategy applied to the local fruit supply chain increased the benefits for ecosystems and society. Emergy indices pointed towards higher efficiency, lower energy appropriation for production, lesser pressure on the environment, and a greater contribution to the local economy. The assessment method used proved to be helpful in evaluating the agricultural chains dynamics, especially, after the introduction of Cleaner Production practices.